Current Status of Chromoendoscopy and Narrow Band Imaging in Colonoscopy - Nass, Jonathan P. (Thieme Medical Publishers, 2010)
Colonoscopy, the preferred procedure for colon cancer screening, has well-documented limitations. To improve colonoscopy's effectiveness, augmented endoscopy techniques, such as chromoendoscopy and narrow band imaging (NBI) have been evaluated. Both techniques are inexpensive, safe, and relatively easy to perform. Chromoendoscopy has an increasingly important role in surveillance of IBD, but significant work is needed to determine the optimal staining techniques and mucosal surface pattern analysis before this technique can be incorporated into routine clinical practice. NBI is a much newer technology with far less data. Well-designed prospective randomized controlled trials have failed to identify a benefit of NBI in screening colonoscopy, in surveillance for high-risk populations or as an adjunct for therapeutic procedures.